A model of atmospheric tide with allowance for hourly variation of ozone density - GIWA , F. B. A.; BABALOLA, M. T. (MAUSAM, 1980)
By using a simplified form of the photochemistry in the ozonosphere, the diurnal variation of ozone density is simulated in the atmosphere, and the tide generated from the resulting absorption of solar radiation is calculated. It is shown that this tide differs significantly from that generated if a constant ozone density is assumed. In particular there is enchancement of the 24 hourly tide and a reduction of the 12 hourly tide.